2021
DOI: 10.2991/assehr.k.210805.169
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parenting Styles on Neuroticism in Young Adults

Abstract: Several studies have shown the risk of neuroticism to mental health and found that one of the factors in shaping personality is parenting styles. To date, however, no studies recorded have specifically examined the role of parenting styles on neuroticism in the Indonesian population. Therefore, this study aimed to provide empirical evidence of the relation between parenting styles and neuroticism in Indonesian young adults. 218 young adults with ages ranging from 18 to 25 years and resided in the Jakarta Metro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, a favourable correlation was discovered between neuroticism and an authoritarian parenting style Metsäpelto & Pulkkinen's (2002). Averina et al (2021) demonstrated that those who had affectionless control-a cold, emotionless upbringing from their parents-scored higher on neuroticism tests than those who had supportive, caring parents, or ideal parenting. Remarkably, the study also discovered a connection between neuroticism scores and the degree of parental protection and care.…”
Section: Neuroticismmentioning
confidence: 99%
“…Additionally, a favourable correlation was discovered between neuroticism and an authoritarian parenting style Metsäpelto & Pulkkinen's (2002). Averina et al (2021) demonstrated that those who had affectionless control-a cold, emotionless upbringing from their parents-scored higher on neuroticism tests than those who had supportive, caring parents, or ideal parenting. Remarkably, the study also discovered a connection between neuroticism scores and the degree of parental protection and care.…”
Section: Neuroticismmentioning
confidence: 99%